2011
DOI: 10.1007/s12291-011-0178-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma: A Case of Atypical Presentation on Protein Electrophoresis

Abstract: Multiple myeloma is a group of B-cell disorders resulting in the secretion of a specific and unique monoclonal immunoglobulin (M-protein). Protein electrophoresis is advised whenever multiple myeloma is suspected. The monoclonal protein migrates as a single entity in the electric field and is detected by the non-specific protein stain as a more intensely stained band superimposed on the usual protein pattern. The M-protein usually migrates in the gamma or beta region of the normal protein pattern; very rarely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…These results were agree with the results of O'connell et al [19] they` found increase amount of γ-globulin [20] and decreasing albumin levels in multiple myeloma patients [12] [19]. M-protein is commonly seen as a restricted band which is frequently observed on γ or β globulin district, also it may be observed on α2 globulin range but this is as very unusual situation [12]. The SPEP is limited at low monoclonal immunoglobulins levels [21], so in order to increase the sensitivity by utilizing of SIFE for diagnosing of the monoclonal immunoglobulins, and to categorize the light or heavy chain isotype, so it should be utilized SPEP and SIFE tests together for the identification of suspected multiple myeloma [13] [22], and to attain additional specific information about the kind of abnormal antibodies present [23].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results were agree with the results of O'connell et al [19] they` found increase amount of γ-globulin [20] and decreasing albumin levels in multiple myeloma patients [12] [19]. M-protein is commonly seen as a restricted band which is frequently observed on γ or β globulin district, also it may be observed on α2 globulin range but this is as very unusual situation [12]. The SPEP is limited at low monoclonal immunoglobulins levels [21], so in order to increase the sensitivity by utilizing of SIFE for diagnosing of the monoclonal immunoglobulins, and to categorize the light or heavy chain isotype, so it should be utilized SPEP and SIFE tests together for the identification of suspected multiple myeloma [13] [22], and to attain additional specific information about the kind of abnormal antibodies present [23].…”
Section: Resultssupporting
confidence: 93%
“…The huge peak of γ-globulin area is sharp relatively. These results were agree with the results of O'connell et al [19] they` found increase amount of γ-globulin [20] and decreasing albumin levels in multiple myeloma patients [12] [19]. M-protein is commonly seen as a restricted band which is frequently observed on γ or β globulin district, also it may be observed on α2 globulin range but this is as very unusual situation [12].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In our patient, the M band on the alpha-2 region was shown to be bound to IgA like a few others. 9,10 So, this case reminds that, M band on alpha-2 region in serum protein electrophoresis can rarely be seen in IgA myeloma patients.…”
mentioning
confidence: 61%
“…Renal failure, defined as a serum creatinine ≥2 mg/dl at the time of diagnosis, is seen in 21% of patients. 9,10 In the patient, the M band on the α 2 region and β region was shown to be bound to IgA. The conventional technique serum electrophoresis is still widely used for the demonstration of M-Protein in the myeloma patient and it remains a gold standard.…”
Section: Discussionmentioning
confidence: 99%